If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4y + 8z + -5x + 5z + -5y = 0 Reorder the terms: 9x + -5x + 4y + -5y + 8z + 5z = 0 Combine like terms: 9x + -5x = 4x 4x + 4y + -5y + 8z + 5z = 0 Combine like terms: 4y + -5y = -1y 4x + -1y + 8z + 5z = 0 Combine like terms: 8z + 5z = 13z 4x + -1y + 13z = 0 Solving 4x + -1y + 13z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + -1y + y + 13z = 0 + y Combine like terms: -1y + y = 0 4x + 0 + 13z = 0 + y 4x + 13z = 0 + y Remove the zero: 4x + 13z = y Add '-13z' to each side of the equation. 4x + 13z + -13z = y + -13z Combine like terms: 13z + -13z = 0 4x + 0 = y + -13z 4x = y + -13z Divide each side by '4'. x = 0.25y + -3.25z Simplifying x = 0.25y + -3.25z
| 2x+38=153 | | mg=4 | | 8(h+67)=-32 | | .6666(x+4)=8 | | 12a-6a^2=-48 | | 12a-6a^2=48 | | 4x+8x+40=304 | | 2x-16=24x+27 | | (2w+3)(8+w)=0 | | -8(u-86)+15=-65 | | p=h+5 | | 19=3(n+2)+1 | | (2x-3)=(x+16) | | 15x-2x+3=10 | | 3p+8-7p= | | -7(5x+5)+4x=3x | | 7y-x=9 | | .024a-8=.224a+2 | | 3(m-8)+-2=8 | | 6x+35=8x+15 | | 8t+2m=w-8 | | -22+t=36 | | -4(2t+2)=-32 | | -4(-6x+1)-3x=1 | | 25z-15=6z-14 | | .03x-3.9=.66 | | 7x+3x=5x+50 | | 8x+8-6x=-6 | | 25z-15=6z-24 | | 4=2(g-11)-2 | | (-7p)3= | | 2=7x-26 |